2011
DOI: 10.1007/s10569-011-9386-7
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the location of a putative distant massive body in the Solar System from recent planetary data

Abstract: We analytically work out the long-term variations caused on the motion of a planet orbiting a star by a very distant, pointlike massive object X. Apart from the semi-major axis a, all the other Keplerian osculating orbital elements experience long-term variations which are complicated functions of the orbital configurations of both the planet itself and of X. We infer constraints on the minimum distance d X at which X may exist by comparing our prediction of the long-term variation of the longitude of the peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 71 publications
0
36
0
Order By: Relevance
“…Model-independent, dynamical constraints on d X were inferred by Iorio (2012) for different values of m X from the upper bounds ∆̟ on the anomalous secular precessions of the longitude of perihelion ̟ of some known planets of the Solar System computed with earlier versions of the INPOP ephemerides (Fienga et al 2010). Iorio (2012) (Iorio 2012), it is straightforward to refine such estimates by using the latest results on ∆̟ obtained with more recent planetary ephemerides (Fienga et al 2011;Pitjeva & Pitjev 2013).…”
Section: Updated Constraints From the Planetary Perihelion Precessionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Model-independent, dynamical constraints on d X were inferred by Iorio (2012) for different values of m X from the upper bounds ∆̟ on the anomalous secular precessions of the longitude of perihelion ̟ of some known planets of the Solar System computed with earlier versions of the INPOP ephemerides (Fienga et al 2010). Iorio (2012) (Iorio 2012), it is straightforward to refine such estimates by using the latest results on ∆̟ obtained with more recent planetary ephemerides (Fienga et al 2011;Pitjeva & Pitjev 2013).…”
Section: Updated Constraints From the Planetary Perihelion Precessionsmentioning
confidence: 99%
“…Iorio (2012) (Iorio 2012), it is straightforward to refine such estimates by using the latest results on ∆̟ obtained with more recent planetary ephemerides (Fienga et al 2011;Pitjeva & Pitjev 2013). From Figure 1 of Iorio (2012), it can be noticed that, for a given value of m X and by keeping the ecliptic latitude β X fixed to some low values, the combined use of the perihelia of Earth, Mars and Saturn allows to constrain effectively d X for practically all values of the ecliptic longitude λ X . In the case m X = 0.7m ⊕ (Iorio 2012), the values by Pitjeva & Pitjev (2013) for the perihelion precessions of Mars and Saturn provide us with overall tighter bounds of the order of d X 350 − 400 AU.…”
Section: Updated Constraints From the Planetary Perihelion Precessionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [28] a ≈ 20% test was reported by using the 5 EGM96 [29] Earth gravity model; subsequent analyses showed that such an evaluation of the total error budget was overly optimistic in view of the likely unreliable computation of the total bias due to the even zonals [30][31][32]. An analogous, huge underestimation turned out to hold also for the effect of non-gravitational perturbations [33] like direct solar radiation pressure, the Earth's albedo, various subtle thermal effects depending on the the physical properties of the satellites' surfaces and their rotational state [31,[34][35][36][37][38][39][40], which the perigees of LAGEOS-like satellites are particularly sensitive to.…”
Section: Introductionmentioning
confidence: 99%